2016
DOI: 10.1038/hdy.2016.64
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of long-distance, insect-mediated pollen movement for a tropical canopy tree species in remnant forest patches in an urban landscape

Abstract: As deforestation and urbanization continue at rapid rates in tropical regions, urban forest patches are essential repositories of biodiversity. However, almost nothing is known about gene flow of forest-dependent tree species in urban landscapes. In this study, we investigated gene flow in the insect-pollinated, wind-dispersed tropical tree Koompassia malaccensis in and among three remnant forest patches in the urbanized landscape of Singapore. We genotyped the vast majority of adults (N=179) and a large numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 46 publications
4
13
0
Order By: Relevance
“…However, we must note that differences between distant donor and distant donor control treatments were not statically significant. Taken together, our results are consistent with those of recent studies (Breed et al, ; Castilla et al, ; Noreen, Niissalo, Lum, & Webb, ; O'Connell, Castilla, Lee, & Jha, ) stressing a critical role of highly‐mobile pollinators for the maintenance of the genetic connectivity and the reproductive processes of highly or obligate outcrossing tree species. Given that P. bourgaeana is pollinated by a diverse array of functional groups (Diptera, Hymenoptera, Coleoptera and Lepidoptera), further studies using paternity analysis may enlighten whether long‐distance pollen dispersal is exclusively performed by specific functional groups of pollinators.…”
Section: Discussionsupporting
confidence: 93%
“…However, we must note that differences between distant donor and distant donor control treatments were not statically significant. Taken together, our results are consistent with those of recent studies (Breed et al, ; Castilla et al, ; Noreen, Niissalo, Lum, & Webb, ; O'Connell, Castilla, Lee, & Jha, ) stressing a critical role of highly‐mobile pollinators for the maintenance of the genetic connectivity and the reproductive processes of highly or obligate outcrossing tree species. Given that P. bourgaeana is pollinated by a diverse array of functional groups (Diptera, Hymenoptera, Coleoptera and Lepidoptera), further studies using paternity analysis may enlighten whether long‐distance pollen dispersal is exclusively performed by specific functional groups of pollinators.…”
Section: Discussionsupporting
confidence: 93%
“…fordii is primarily by pollen dispersal. As both mp and dp are directly related to the sizes and degrees of isolation of areas, they should vary among species and populations within species with similar pollination insects (Braga & Collevatti, ; Manoel et al, ; Monthe, Hardy, Doucet, Loo, & Duminil, ; Noreen et al, ; Sebbenn et al, ; Tambarussi, Boshier, Vencovsky, Freitas, & Sebbenn, ). For example, for a Neotropical tree Copaifera langsdorffii in a highly isolated and fragmented forest fragment (4.8 ha), Manoel et al () found its mp and dp values were 0.08 and 66 m, respectively; while for a tropical tree Entandrophragma cylindricum in a relatively large and continuous forest, Monthe et al () found its mp and dp values were 0.32–0.40 and 506–540 m, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we consider the pollen flow in the population of TB village moderate. Because pollination insects, such as bees, could carry pollen to very long distances (Braga & Collevatti, ; Dick, Etchelecu, & Austerlitz, ; Manoel et al, ; Noreen et al, ; Sebbenn et al, ; Tambarussi et al, ), it is possible to find larger mp and dp in larger and more continuous populations of E . fordii than those in our study, based on pollen‐mediated gene dispersal capacities of E .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, observations of floral visitors in the field (flies beetles and tiger moths in particular) suggest that the species may be largely insect-pollinated. While there is record of long-distance insect-mediated dispersal of pollen in the order of hundreds of kilometers (Ahmed, Compton, Butlin, & Gilmartin, 2009), long-distance dispersal of pollen by insects usually ranges from hundreds of meters to a few kilometers (Jha & Dick, 2010;Millar, Coates, & Byrne, 2014;Noreen, Niisalo, Lum, & Webb, 2016;White, Boshier, & Powell, 2002).…”
Section: Genetic Structure and Dispersalmentioning
confidence: 99%